Catalytic Enantioselective Desymmetrization of meso-Cyclopropane-Fused Cyclohexene-1,4-diones by a Formal C(sp2)–H Alkylation - Ray, Sayan; Mukherjee, Santanu (Synlett, 2022)
A bicyclo[4.1.0]heptane framework consisting of cis-fused cyclopropane and cyclohexane rings is found in several bioactive compounds. Given the symmetry of this core, catalytic desymmetrization can be considered as the most straightforward strategy for its enantioselective synthesis. Known desymmetrization reactions of meso-bicyclo[4.1.0]heptane derivatives proceed with opening of the cyclopropane ring. We now report the first ring-retentive desymmetrization of bicyclo[4.1.0]heptane derivatives, namely meso-cyclopropane-fused cyclohexene-1,4-diones, through a formal C(sp2)-H alkylation using a nitroalkane as the alkylating agent. This reaction is catalyzed by a dihydroquinine-derived bifunctional tertiary aminosquaramide and generates the products with up to 97:3 er. An application of this reaction is demonstrated by the first catalytic enantioselective synthesis of the natural product (–)-car-3-ene-2,5-dione.
Keywords: organocatalysis; desymmetrization; cyclopropanes; bicycloheptanes; fused ring systems